Experimental and numerical investigations of CFRP reinforced masonry ?beams performance under bending loads - Mahmoud Zaghlal; Alaa El-Sisi; Mohamed Husain; Samar Samy (Fracture and Structural Integrity)
In this paper, an experimental and numerical study was achieved to investigate the behavior of masonry beams internally reinforced using carbon fiber-reinforced polymer (CFRP) and hybrid steel/CFRP reinforcements. Three beams were built using concrete bricks and grout mortar. The brick was designed with two holes that were filled with grout before placing the rebar inside. One beam was built without shear reinforcement, and the other two were with shear reinforcement. Material characterization tests were performed to evaluate the compressive strength of the brick and the masonry cube and the flexural strength of the masonry prism. The masonry cubes were prepared and tested to evaluate their equivalent mechanical properties. The beams were tested in three-point bending with an effective simply supported span of 840 mm where the load deformations and failure loads were monitored. Finite element models were built using ANSYS and validated with experimental results. Additional beam models were analyzed to study the effect of shear reinforcement spacing from 0.78d to 0.39d and more hybrid reinforcement configurations. Results showed that using equivalent material properties in numerical modeling instead of modeling bricks and mortar was acceptable. In addition, using shear reinforcement with a spacing of 0.78 d didn't enhance the shear behavior of the spacing. Finally, the hybrid steel/CFRP-reinforced beam with shear reinforcement achieved the highest capacity compared to the two other beams.